2020
DOI: 10.1108/tg-01-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

An examination of citizen satisfaction with mandatory e-government services: comparison of two information systems success models

Abstract: Purpose The purpose of this study is to empirically examine the utility of information systems (IS) success models in mandatory e-government services, as opposed to the volitional ones that have been the focus of previous studies. The models include the technology acceptance model (TAM) (1989) and Seddon’s model (1997), which involve three (ease of use, usefulness and citizens satisfaction) and four variables (system quality, information quality, usefulness and citizen satisfaction). Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 80 publications
0
14
0
2
Order By: Relevance
“…Our results are in line with other models on e-service adoption developed by [76], which stress the importance of learning and previous visits for further usage. E-government is becoming mandatory in many countries, as part of the transformation of public services, and citizens are thus forced to interact with the government using these applications [77][78][79], so the development of digital skills is increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with other models on e-service adoption developed by [76], which stress the importance of learning and previous visits for further usage. E-government is becoming mandatory in many countries, as part of the transformation of public services, and citizens are thus forced to interact with the government using these applications [77][78][79], so the development of digital skills is increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…This study has acknowledged the incredible work done by previous scholars have continued to propose and develop e-government frameworks (Malodia et al, 2021;Ahmad et al, 2021;Singh et al, 2020;Roblek et al, 2020;Dias, 2020), e-government readiness assessment tools (Alghamdi, Goodwin & Rampersad, 2016;Assefa et al, 2021;Kagoya & Gilbert, 2020;Haydari, 2020;Pal, Singh & Dhaliwal, 2020). And other studies have suggested models for egovernment implementation (Elbahnasawy, 2021;Li & Xue, 2021;Sharma et al, 2021;Li, 2021;Alkraiji, 2020). In spite of the great empirical literature provided by preceding authors in line with e-government, there is has not been a study addressing the a multigroup analysis of the key salient determinants for e-government implementation success in developing countries like Uganda and Tanzania.…”
Section: Introductionmentioning
confidence: 67%
“…With regard to the study conducted by the authors (Alkraiji, 2020;Ameen et al, 2019;Cho et al, 2019) the results showed that there is a positive relationship between system quality and information quality, which indicates its importance in measuring the success of e-government. Therefore, the following hypothesis can be suggested:…”
Section: Electronic Government Systemmentioning
confidence: 92%